How Different Mulch Materials Regulate Soil Moisture and Microbiological Activity? - Papdi, Enikő; Veres, Andrea; Kovács, Flórián; Juhos, Katalin (Journal of Central European Green Innovation, 2022)
As a result of climate change, the frequency of droughts across Europe is showing an increasing trend. The solution to this problem can be various soil cover techniques, which help to preserve soil moisture and soil biological activity, thereby increasing crop yield. In our research, we examined how different mulch materials affect the regulation of soil moisture and the microbiological activity of the soil. The experiments were set up on two sites: a sandy soil with a low soil organic matter content (Királyhalom, Serbia) and an coarse loamy soil with a higher water capacity (Thessaloniki, Greece). The treatments were set up in 4 repetitions with pepper plants (Capsicum annuum L.). Daily intensive irrigation with wool mulch, agrotextile, straw mulch and control treatments was used on the Serbian site. The irrigation was carried out every 6 days at the Greek site, where the treatments were as follows: wool mulch with plants, wool mulch without plants, plants without mulch and the control without plants. The yield was measured, and the moisture content, β-glucosidase activity and active (permanganate oxidizable) carbon content of the soils at the time of sampling were examined every 2 weeks. In the Serbian area, wool mulch showed significantly lower β-glucosidase activity compared to the other treatments. This was presumably due to the good water absorption capacity of the wool mulch and the fact that the soil could not aerate in addition to the intensive irrigation, thus the enzyme activity decreased. All mulch treatments increased the active carbon content compared to the untreated control, with the straw mulch to the greatest extent. In the extensively irrigated Greek soil, β-glucosidase was significantly higher in pepper plots covered with wool mulch compared to the control area without plants, but also higher compared to pepper plots not covered with wool mulch. The higher yield results measured on the mulched plots indicate that, in addition to water retention, biological activity also plays a major role in the development of yields. The effect of each mulching method on soil biological activity depends on the degradability of the mulch material, the frequency of irrigation, and the soil's water-holding capacity.